Determinants of the adoption of biological control agents in Andhra Pradesh - Vennelasree, V; Divya, K; Uma, K; Prahadeeswaran, M; Ashok, K G (Plant Science Today, 2025)
This study, conducted in the Kurnool district of Andhra Pradesh, India, in 2024, explored the factors influencing farmers' adoption of biological control agents (BCAs). Kurnool, an agriculturally significant region, was divided into four clusters: Kallur, Pathikonda, Kodumur and Panyam. A total of 120 farmers were selected using a convenience sampling method, chosen due to logistical constraints and the exploratory nature of the research. Data were gathered through semi-structured household interviews and supplemented by key informant discussions to provide additional context. The study examined adoption of BCAs as the dependent variable, with independent variables including age, gender, education, primary occupation, farming experience, farm income, farm size, training and membership in agricultural organizations. Analysis using a forward stepwise logistic regression model identified farm size, annual income and training as significant positive factors influencing awareness and adoption of BCAs. Results showed that 25 % of the sampled farmers were using BCAs. Key barriers to adoption included a lack of knowledge, reliance on chemical fertilizers due to entrenched agricultural practices, high costs and limited access to credit. To address these challenges, the study recommends implementing targeted education programs, enhancing access to affordable credit and fostering cooperative networks and public-private partnerships to strengthen collaboration between farmers and agricultural organizations. The findings emphasize the need for comprehensive policy measures to support sustainable agricultural practices through the promotion of BCAs.